Healthy Parent Carers programme: mixed methods process evaluation and refinement of a health promotion intervention - Lloyd, J; Bjornstad, G; Borek, A; Cuffe-Fuller, B; Fredlund, M; McDonald, A; Tarrant, M; Berry, V; Wilkinson, K; Mitchell, S; Gillett, A; Logan, S; et al. (BMJ Publishing Group, 2021)
Objectives Parent carers of children with special educational needs or disability are at risk of poorer mental and physical health. In response to these needs, we codeveloped the ‘Healthy Parent Carers’ (HPC) programme. This study examined the views and experiences of participants in the HPC feasibility trial to inform programme refinement.